Neural bases of freedom and responsibility - Gruart, Agnès; Delgado-García, José M. (Frontiers in Neural Circuits, 2023)
This review presents a broad perspective of the Neuroscience of our days with special attention to how the brain generates our behaviors, emotions, and mental states. It describes in detail how unconscious and conscious processing of sensorimotor and mental information takes place in our brains. Likewise, classic and recent experiments illustrating the neuroscientific foundations regarding the behavioral and cognitive abilities of animals and, in particular, of human beings are described. Special attention is applied to the description of the different neural regulatory systems dealing with behavioral, cognitive, and emotional functions. Finally, the brain process for decision-making, and its relationship with individual free will and responsibility, are also described.